Relationships among Antecedents, Processes, and Outcomes for Shared Decision Making: A Cross-Sectional Survey of Patients with Lumbar Degenerative Disease. (April 2022) - Chen, Chia-Hsien; Chuang, Hsin-Yi; Lee, Yen; Elwyn, Glyn; Hou, Wen-Hsuan; Kuo, Ken N.
Background: Among musculoskeletal disorders, lumbar degenerative disease (LDD) is the leading cause of total disability-adjusted life years globally. Clinical guidelines for LDD describe multiple treatment options in which shared decision making becomes appropriate. Objectives: To explore the relationships among measures of decision antecedents, process, and outcomes in patients with LDD. Methods: Patients with LDD were recruited from outpatient clinics in a teaching hospital in Taiwan and administered surveys to collect measures of decision antecedents, processes, and outcomes. Multiple linear regression was conducted to assess the association between decision antecedents and the decision making process. Hierarchical linear regression was conducted to assess the relationships among decision antecedents, the decision making process, and decision outcomes. Results: A total of 132 patients (mean age, 61 years) completed the survey. After adjustment for personal factors, 2 decision antecedents (namely, decision making self-efficacy and readiness) significantly predicted patients' experiences of engaging in shared decision making (SDM). Decision making readiness and process were associated with fewer decisional conflicts and greater decision satisfaction. Limitations: Models derived from cross-sectional surveys cannot establish causal relationships among decision antecedents, decision making processes, and decision outcomes. Conclusions: Our results support the SDM framework, which proposes relationships among decision antecedents, the decision making process, and decision outcomes.